2022
DOI: 10.1007/s10610-022-09525-7
|View full text |Cite
|
Sign up to set email alerts
|

“In Police We Trust?”—Confidence in the Police Among Adolescents With and Without a Migration Background in Germany

Abstract: Overall, adolescents exhibit a high level of confidence in the police. Nevertheless, it is problematic when certain social groups show lower levels of confidence in the police as this can affect police legitimacy. Based on a representative survey of ninth-grade students in Lower Saxony (N = 12,444), conducted in 2019, the current study examines confidence in the police among adolescents with and without a migration background. As well as an examination of the correlation, the study analyses whether the lower r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Recently, some studies have examined the relationships between demographic factors and trust in the police [49][50][51][52]. Some studies investigated and found an association between age and trust in the police [21,[24][25][26][27][28][29].…”
Section: Age and Trust In The Policementioning
confidence: 99%
“…Recently, some studies have examined the relationships between demographic factors and trust in the police [49][50][51][52]. Some studies investigated and found an association between age and trust in the police [21,[24][25][26][27][28][29].…”
Section: Age and Trust In The Policementioning
confidence: 99%